Making of Laloo Yadav - "Thakur, Sankarshan" (New Delhi, 2000)
India has perhaps not seen a politi cian quite like Laloo Yadav, a mes merising bundle of odds-hero to some, villain to others, self-fashioned champion of the underdog and yet more imperious than the most well-heeled feudal, charming and ruthless by turns, a simpleton when he wants to be one, a manipulator when he needs to be. A leader who has repeatedly defied predictions of doom, and who is not finished yet with the business of leaving his imprint on politics and society. Here, for the first time, is the fascinating story of the rise of Laloo Yadav...and the fall of Bihar, a state different from any other in the abject acceptance of its wretchedness, in its fracture of will to change. A brilliant account seen through the sharp and unsparing journalistic eye of Sankarshan Thakur. This is neither a hatchet job nor a hagiography, but a plain tale of a complex populist and what his brand of politics does to people.
Keywords: Statesman-India-Bihar-Biography